Detector development for spin-echo SANS techniques using ZnS:Ag/6LiF and 6Li glass scintillators - Giacomo Mauri; G. Jeff Sykora; Gregory N. Smith; Steven R. Parnell; Robert M. Dalgliesh; Dirk Honecker; Sarah E. Mann; Erik M. Schooneveld; Nigel J. Rhodes (Scientific Reports)
Abstract Neutron spin-echo techniques exploit Larmor precession of the neutron spin to encode either the scattering angle or energy. These are powerful means to extend the measurable momentum transfer (Q) and energy (E) range in neutron scattering measurements. Standard small-angle neutron scattering (SANS) instruments are sensitive in a range of $$≈$$ ≈ 10–200 nm, whereas these techniques allow the study of structures in materials on length scales of tens of nm up to tens of $$\upmu$$ μ m. The Larmor instrument at ISIS is equipped to operate in spin-echo modulated SANS (SEMSANS) and spin-echo SANS (SESANS) mode. Two separate detectors were developed to cope with the performance demands set by these techniques. The first is a position sensitive ZnS:Ag/6LiF scintillator-based detector coupled with wavelength shifting fibres that can be used for both SEMSANS and SESANS. A detector prototype using GS20 glass scintillator directly coupled to a multi-anode photomultiplier was developed as an alternative for SESANS measurements at higher incident neutron fluxes. The designs and results obtained with the two detectors are presented together with future improvements to both technologies. These, in addition to promising development routes, demonstrate the potential for utilising a WLSF ZnS:Ag/6LiF scintillator detector and a pixelated GS20 detector for SEMSANS and SESANS applications.